The Avars: A Review of Their Ethnogenesis and History - Emil Heršak; Ana Silić (Migracijske i etničke teme, 2002)
In this paper, the authors present an extensive review of the ethnic history of the Avars, beginning from the time of their predecessors on the borders of China. The origin of the Avars is reviewed from the Rouran age to the time of crisis among the Turkic kaganates in Central Asia. On the basis of a common typology of Eurasian nomadic peoples, the authors see the Avars as a complex group, composed of many ethnic fragments: Heftalites and various Central Asian Iranian groupings that were assimilated by the Oguric Turks, the descendents of the Huns, possibly some Mongolic elements tied to the original Rouran, the Pontic Bulgars, and perhaps some Ugric populations. During the final phase of Avar settlement in Pannonia, they were joined by some Germanic and Slavic tribes. In the continuation of their text, the authors note the historical development during the first and second Avar kaganate (i.e. the kaganate at the time of Bayan's dynasty and the kaganate in the period of temporary revival following the defeat of the Avars at Constantinople in the first quarter of the 7th century). Relations were especially complex with Byzantium, the Slavs, the Langobards, and with the Franks, who would finally destroy the independent Avar state in Pannonia. The authors also briefly treat the problem involving the relations between the Avars and the Croats. Historical sources explicitely claim that an Avar group survived in Croatia at least until the middle of the 10th century. The Avars were ultimately absorbed by new arrivals in Pannonia – the Magyars, as well as by the surrounding peoples, mainly Bulgars and Croats. Nevertheless, the Avars remain to the present day an ethno-historical enigma. To the present day it is impossible to answer the question: Who exactly were the Avars? In the long-run, they were probably political heirs of the Rouran state, yet on the basis of very slight linguistic indicators, one could conclude that the initial core population that left Central Asia was composed mainly of Oguric peoples, with a strong Iranic substratum. The Avars played a vital role in the Slavic migrations and settlements in South-East Europe.